REVIVING THE ISLAMIC MARKET: IMAM AL-GHAZALI'S PRINCIPLES FOR FAIR AND ETHICAL ECONOMIC TRANSACTIONS - Sumpena, Mochamad; Hikmah, Nurul (NATUJA: Jurnal Ekonomi Syariah, 2025)
The concept of the market has existed since the time of the Prophet Muhammad SAW and has undergone significant transformations, especially in the era of Industry 4.0. This research examines the Islamic market mechanism as outlined by Imam Al-Ghazali, with a focus on the principle of tauhid. In contrast to capitalist views that advocate for a free market with minimal government intervention, Al-Ghazali's perspective integrates divine principles and ethics into economic transactions. The study utilizes a qualitative, descriptive approach to analyze secondary data from various sources, aiming to highlight how Islamic teachings can create a fair and balanced market environment. Al-Ghazali's principles suggest that a just market is founded on honesty, fairness, and mutual assistance, guided by religious values. This paper also discusses the ethical implications of market practices, urging businesses to align their activities with Islamic values to ensure long-term prosperity and divine blessing. While this study focuses on Al-Ghazali's views, future research should compare these with contemporary economic theories to deepen understanding of Islamic market mechanisms in modern economies.